A study on factors affecting employee turnover intention among Generation Z in fast-food industry - Khor, Wei Man; Lum, Li Heng; Too, Jing Yu; Yap, Chen Mun (2024)
Employee turnover is a global concern, with many individuals leaving their jobs each year, often with the intention to quit. High turnover rates can result in lost training investments, higher recruitment costs, and the loss of valuable employees. Generation Z, born between 1995 and 2012, possesses technological proficiency, high salaries, and flexible work conditions, leading to high turnover rates in the fast food industry. This research delves into the factors influencing the turnover intentions of Generation Z employees within the fast-food sector, examining job stress, job stressors, job satisfaction, and organizational commitment as crucial independent variables. Drawing on the Job Demands-Resources (JD-R) theory and the Social Exchange Theory (SET), this study explores the dynamics shaping the intentions of Generation Z employees to leave their fast-food jobs. The targeted sample size of 384 employees from Generation Z in the fast-food industry to learn more about their viewpoints and experiences. A thorough reliability test was conducted on the questionnaire to verify the robustness of the study instrument. The study performed inferential analysis and multiple regression analysis to find significant relationships between the independent factors and the dependent variable. The results were analysed using the Statistical Package for the Social Sciences (SPSS). Our study enriches the understanding of intricate interactions between turnover intentions and job-related characteristics within the growing Generation Z workforce. It sheds light on the stresses they face, their levels of job satisfaction, and their commitment to their respective organizations. The knowledge garnered from this research can inform strategies to mitigate turnover rates, retain valuable employees, and enhance the sustainability of the fast-food workforce.